Sports Mentoring: Review of literature - Κοσματόπουλος, Ανδρέας Δημήτριος (Πανεπιστήμιο Πελοποννήσου, 2014)
The concept of mentoring has various definitions and practices depending on the field, the people involved and the aims that need to be achieved. It contains notable age, hierarchical authority, and experience differences between mentors and mentees. The purpose of the study was to examine the current situation in sports mentoring and to provide a holistic approach where mentoring can be applied in sports coaching as an undivided element. The methodology used included a review of the literature from a wide range of fields. The major results of the study were that although few sport mentoring formal programs exists, where those applied, can become a valuable tool in the athlete’s development both as a performer and well-being. Criticism and concerns on mentoring arise for its efficiency and the impact can have at people’s lives. It was concluded that sport mentoring is an evolving relationship that requires time and attention to develop and includes successes and challenges.
Keywords: Φυσική αγωγή και εκπαίδευση; Physical education and training; Mentoring; Mentor; Mentee; Sport Mentoring; Καθοδήγηση; Μέντορας; Καθοδηγούμενος; Αθλητική Καθοδήγηση